FILSAFAT ILMU SEBAGAI LANDASAN PENGEMBANGAN KOMPUTER MENUJU KOMPUTER VISION - Herdianto Herdianto; Muhammad Zarlis; Zulkifli Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
In the philosophy of science, humans are seen as thinking creatures, with human philosophy, they can make major changes to the economic system that was originally agrarian to industrial. This change occurred in England and caused the industrial revolution. Based on the statement above, the purpose of this article is to explain the importance of understanding the philosophy of science for a human being in general and a true thinker in particular in an effort to make the philosophy of science the foundation and support for life in the development of science in general and computer vision in particular. with very high speed, memory, capability and other facilities, it is widely used in various fields including industry to handle jobs that are dangerous, require high accuracy and are monotonous. Furthermore, due to technological developments and human activities that are increasingly dense and require high mobility, the automotive industry develops autodriver cars. To support this autodriver, research topics that continue to be developed related to computer vision are object detection and distance measurement using a digital camera. It is hoped that based on the philosophy of science in conducting distance measurement research using a digital camera, optimal results can be obtained.